Production of furfural from xylose, water-insoluble hemicelluloses and water-soluble fraction of corncob via a tin-loaded montmorillonite solid acid catalyst. (January 2015) - Li, Huiling; Ren, Junli; Zhong, Linjie; Sun, Runcang; Liang, Lei
Graphical abstract: Highlights: The conversion of xylose and pentose-rich carbohydrate to furfural was performed. Sn-MMT with double acid sites was used as a heterogeneous catalyst. 76.79% furfural yield and 82.45% selectively were obtained from xylose. 39.56% and 54.15% furfural yields were directly obtained from WIH and WSF. Abstract: The conversion of xylose, water-insoluble hemicelluloses (WIH) and water-soluble fraction (WSF) of corncob to furfural was performed using montmorillonite with tin ions (Sn-MMT) containing double acid sites as a solid acid catalyst. The co-existence of Lewis acids and Brønsted acids in Sn-MMT was shown to improve the furfural yield and selectivity. 76.79% furfural yield and 82.45% furfural selectivity were obtained from xylose using Sn-MMT as a catalyst in a biphasic system with 2-s-butylphenol (SBP) as the organic extracting layer and dimethyl sulfoxide (DMSO) as the co-solvent in contact with an aqueous phase saturated with NaCl (SBP/NaCl-DMSO) at 180 °C for 30 min. Furthermore, Sn-MMT also demonstrated the excellent catalytic performance in the conversion of pentose-rich materials of corncob and 39.56% and 54.15% furfural yields can be directly obtained from WIH and WSF in the SBP/NaCl-DMSO system, respectively.